2016
DOI: 10.1523/jneurosci.0902-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Neural Markers of Responsiveness to the Environment in Human Sleep

Abstract: Sleep is characterized by a loss of behavioral responsiveness. However, recent research has shown that the sleeping brain is not completely disconnected from its environment. How neural activity constrains the ability to process sensory information while asleep is yet unclear. Here, we instructed human volunteers to classify words with lateralized hand responses while falling asleep. Using an electroencephalographic (EEG) marker of motor preparation, we show how responsiveness is modulated across sleep. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
113
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 65 publications
16
113
1
Order By: Relevance
“…Memory reactivation was facilitated when the cue was followed by a spindle, as evidenced both by later memory performance and by EEG analyses. Moreover, this paradigm -using lateralized differences as a means of tracking reactivation of specific episodic associations -could be useful for uncovering nuanced relationships between reactivation and memory (Lewis-Peacock and Norman, 2014) and investigating how reactivation differs across physiological states (Andrillon et al, 2016;Jiang et al, 2017;Schönauer et al, 2017;Belal et al, 2018) and human populations (Mander et al, 2013;Westerberg et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory reactivation was facilitated when the cue was followed by a spindle, as evidenced both by later memory performance and by EEG analyses. Moreover, this paradigm -using lateralized differences as a means of tracking reactivation of specific episodic associations -could be useful for uncovering nuanced relationships between reactivation and memory (Lewis-Peacock and Norman, 2014) and investigating how reactivation differs across physiological states (Andrillon et al, 2016;Jiang et al, 2017;Schönauer et al, 2017;Belal et al, 2018) and human populations (Mander et al, 2013;Westerberg et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several prior findings suggest that lateralized neural signals can be tracked with EEG. After training participants to perform lateralized judgments on words during wake (e.g., "press left if word, press right if nonword"), corresponding lateralized responses were elicited by those stimuli during sleep (Kouider et al, 2014;Andrillon et al, 2016). This finding shows that participants can apply a well-learned task set (acquired during wake) to stimuli presented during sleep, but does not show retrieval of specific episodic memories.…”
Section: Introductionmentioning
confidence: 85%
“…The reduction in the diversity of subjective experiences during these 'diminished' states may plausibly be reflected in the diversity of neural signals in these states. Indeed, measures of spontaneous EEG signal diversity, such as Lempel-Ziv complexity, are reduced in states with diminished or absent conscious experience, such as during sleep or under anaesthesia, relative to the normal waking state [5][6][7] . In a more direct test of the relation between experiential diversity and neuronal signal diversity, Schartner et al, 8 reported a brain-wide robust increase in signal diversity during altered states of consciousness (ASC) induced by the classic psychedelics LSD, ketamine and psilocybin.…”
Section: Introductionmentioning
confidence: 99%
“…Promising results of the PCI studies encouraged researchers to investigate similar properties in the spontaneous brain activity recorded during different states of consciousness. Similarly to PCI, diversity of spontaneous EEG signals is high during wakefulness and drops during propofol anesthesia or NREM sleep (Schartner et al, 2015(Schartner et al, , 2017Andrillon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%